Revisiting Physical Properties of Mock Globular Cluster Tidal Tails - Andrés E. Piatti (The Astrophysical Journal)
In this work, we present results of the first in-depth analysis of extra-tidal mock stars of Milky Way globular clusters recently generated by S. M. Grondin et al. Particularly, we selected a sample of globular clusters with a general consensus of being formed in the bulge or in the disk of the Milky Way. From the catalog, we estimated the width and the dispersion in the z -component of the angular momentum and in the line-of-sight and tangential velocities of their tidal tails, and compared the results with those predicted by cosmological simulations of K. Malhan et al. and observations. We found that the resulting values of these four quantities are not in agreement with an in situ formation of the associated globular clusters. On average, the resulting widths agree with an in situ origin, while the dispersion in the z -component of the angular momentum, and the dispersion in the line-of-sight and tangential velocities fail in matching this formation scenario. The four quantities derived for globular clusters formed in the bulge or in the disk show similar correlations with the stream length, namely, the width and the dispersion in the z -component of the angular momentum increase with the stream length, while the bulk of dispersion values in the line-of-sight and tangential velocities is around 12 km s ^−1 along the mock stream.